2002
DOI: 10.1103/physrevb.65.045413
|View full text |Cite
|
Sign up to set email alerts
|

Connective neck evolution and conductance steps in hot point contacts

Abstract: Dynamic evolution of the connective neck in Al and Pb mechanically controllable break junctions was studied during continuous approach of electrodes at bias voltages V_b up to a few hundred mV. A high level of power dissipation (10^-4 - 10^-3 W) and high current density (j > 10^10 A/cm^2) in the constriction lead to overheating of the contact area, electromigration and current-enhanced diffusion of atoms out of the "hot spot". At a low electrode approach rate (10 - 50 pm/s) the transverse dimension of the neck… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
37
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 36 publications
3
37
0
Order By: Relevance
“…As to Joule heating, the temperature rise in a nanocontact due to electron energy dissipation is still a matter of controversy [1], and no definite results have been established on the contact temperature under high-bias/high-current conditions. On the other hand, electromigration of atoms have been experimentally observed in atom-sized contacts under high biases [8,9], and two-level fluctuations (TLF) in conductance were reported on some metal nanocontacts at low temperatures [8,10,11]. Although these previous observations of TLF suggest that our conductance fluctuations are likely due to electromigration, no detailed analyses can be made at this time since electromigration is a thermally activated process but we lack information on the contact temperature.…”
Section: Discussionmentioning
confidence: 50%
“…As to Joule heating, the temperature rise in a nanocontact due to electron energy dissipation is still a matter of controversy [1], and no definite results have been established on the contact temperature under high-bias/high-current conditions. On the other hand, electromigration of atoms have been experimentally observed in atom-sized contacts under high biases [8,9], and two-level fluctuations (TLF) in conductance were reported on some metal nanocontacts at low temperatures [8,10,11]. Although these previous observations of TLF suggest that our conductance fluctuations are likely due to electromigration, no detailed analyses can be made at this time since electromigration is a thermally activated process but we lack information on the contact temperature.…”
Section: Discussionmentioning
confidence: 50%
“…The most important result is that the conductance histogram shows peaks close to integer multiples of the conductance quantum. 8,27,28 Here, the peak-to-valley ratio is smaller than in experimental conductance histograms, but this could be caused by the relatively small number of configurations used in our calculations. Also, the statistical analysis could improve by taking into account different orientations of the nanowire main axis.…”
mentioning
confidence: 65%
“…8,[10][11][12] The latter two properties, in particular, are of key importance in understanding the stability of atomic wires under current flow. 12 Halbritter et al 13 and, more recently, Mizobata et al 14,15 have explored the mechanical stability of atom-sized Al wires. These authors found that the probability of forming single-atom contacts decreases with increasing bias and that it vanishes at a critical bias of about 1 V. 16,17 In addition, several samples exhibited low-bias instabilities ͑typically at biases of 100 mV or less͒ leading to breakup of the atomic wires.…”
mentioning
confidence: 99%